Modulation of growth-related protein expression of native chicken in low altitude in West Jawa, Indonesia - Mushawwir, Andi; Adriani, Lovita; Permana, Ronnie; Arifin, Johar; Vega, Renato S A (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The objective of this study was to evaluate the response-ability of local chickens to their rearing habitat, especially at low altitudes, to comprehensively understand the cellular response related to protein growth. Materials and Methods: Studies of cellular responses related to modulation and growth-related protein salinization for three local Indonesian chicken breeds to low altitudes with high temperatures have been conducted in two locations with altitudes <55 m above sea level. Three hundred local chickens, each consisting of one hundred Sentul, Kedu, and Pelung chickens. During the study, chickens were kept in an intensive system with litter control, equipped with access to play. Blood samples were collected following all standard procedures at the end of the study. Analysis of blood samples has been carried out based on procedures by the protocol on the BioSource KIT and Randox KIT. Results: Based on the results of the current study, it appears that the overall cellular response of three local chicken breeds shows differences. Sentul chicken and Pelung chicken have better cellular protein expression responses than Kedu chicken. However, when it comes to body weight growth, it seems that protein irradiation to growth is better in Kedu chicken. Conclusion: The results of the study showed that low altitude with high ambient temperature was better able to be responded to by Kedu chickens, while Sentul and Pelung chickens resulted in both experiencing metabolite shocks, which can be characterized by increased alternative energy provision with creatine phosphate change activity. J. Adv. Vet. Anim. Res., 11(4): 880–887, December 2024 http://doi.org/10.5455/javar.2024.k839